2002: A Justice Odyssey - Economides, Kim (Victoria University of Wellington Law Review, 2003)
Professor Economides, 2002 Chapman Tripp visiting fellow, overviews research on the supply side of the access to justice equation. Economides argues that the justice equation is based on the nature of supply and demand for legal services and the nature of the claim that clients wish to bring to a legal forum. However, the access to justice theme is moved beyond the supply side and into questions regarding the quality of the access provided suggesting that there is a need to explore the understandings of justice held by members of the legal profession and legal ethics, and the role that law schools and legal education have in formulating these.